Análise da aplicação do sistema de triagem de manchester na estratificação de risco em idosos acolhidos em estabelecimento assistencial de saúde público - Guimarães, José Flávio Viana (2020)
Hospital medical emergency sectors apply risk classification models and systems to define no care for the population assigned to the establishment of health care assistance (HCE). The Manchester Triage System (MTS) defines maximum waiting times for medical emergency department staff to respond to each risk, prioritizing the most serious cases over less serious cases. Considering the increase in the elderly population (people aged 60 or over, for developing countries like Brazil) and the specifics of the phenomenon in this population (comorbidities, higher mortality rates from chronic degenerative diseases with functional repercussions, low clinical resilience and fragility, iatrogenesis, atypical clinical manifestations of common diseases and polypharmacy); the objective was to analyze the performance of the MTS risk classification, in elderly people seen in the medical emergency department of a public HCE, tertiary health care and large scale. The data were selected through the secondary source, chosen for convenience, in the HCE Medical Archive sector. The elderly group was divided according to an age group at 5-year intervals. Use the statistical method of odds ratio and 95% confidence interval to determine the performance of the MTS risk classification among the elderly. The results obtained were represented by forest plots. The results of statistical statistics demonstrate higher frequencies of hospitalization outcomes among elderly people classified as very urgent (orange) - 42.56% and urgent (yellow) - 39.49%. The older the age group, the lower the frequency of hospitalization, a result that does not corroborate with the findings of the international literature compared. Regarding the results of the inference of the performance of the MTS risk classification, through the odds ratios and confidence intervals, the statistical differences between the age groups of the elderly are not obtained for the internal outcome, comparing them to the MTS risks classification. According to the results obtained, it was not possible to relate a greater probability of hospitalization among the age groups of elderly people with an MTS risk classification, so that there is a need for further studies to test the performance of MTS in the elderly, for the hospitalization outcome. It was concluded that the result may be suitable for the MTS risk classification analysis.